Factors affecting foreign direct investment in ASEAN: https://doi.org/10.69692/SUJMRD100408 - Souphilay, Luangphaxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study examines the changes in trade openness, gross domestic product (GDP), and foreign direct investment (FDI) in ASEAN from 1999-2022, analyzing how trade openness and GDP impact FDI. Using geographic data and descriptive statistics, the study employs the Panel Fully Modified Least Squares (FMOLS) method. The analysis reveals that since 1999, trade openness in ASEAN has generally increased, driven by trade liberalization, international trade agreements, and infrastructure development. However, there have been occasional declines due to specific events. GDP has also consistently risen due to increased FDI, trade openness, and infrastructure improvements, transitioning the ASEAN economies from agriculture to manufacturing and services, leading to more global exports. FDI has shown continuous growth, supported by trade openness and infrastructure development, which have enhanced the region's attractiveness for investment. The study finds a positive relationship between trade openness, GDP, and FDI in ASEAN. A 1% increase in GDP leads to a 5.27% rise in FDI at a 1% significance level, while a 1% increase in trade openness results in a 2.62% increase in FDI at a 5% significance level.